ANALISIS PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK INSAN UTAMA 2 KECAMATAN TAMPAN KOTA PEKANBARU - Visvidya Husna Pratiwi; Daviq Chairilsyah; Wusono Indarto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: An initial observation of the moral behavior of children aged 5-6 years in Taman Kanak-kanak Insan Utama 2 shows that some children not in accordance with general moral values in the vicinity. The moral behavior which is not in accordance with the applicable around such as children do not appreciate his friend’s work, do not say thank you when somebody given he something, wouldn’t be patient to wait their turn, do not listen when others talk to him, wouldn’t give aid to whose need his help, annoying his friends, speak loudly, and do not say sorry when do a mistake. This study aimed to analyze the moral behavior of children aged 5-6 years in Taman Kanak-kanak Insan Utama 2 Tampan Districts of Pekanbaru City. The sample used in this research were 27 children. The data collection techniques were used observation. Data were analyzed using a percentage formula by entering the number of scores achieved divided by the maximum score and then multiplied by 100%. The results of the eight items obtained statement that the moral behavior of children aged 5-6 years in Taman Kanak-kanak Insan Utama 2 are in